Translocator protein in late stage Alzheimer's disease and Dementia with Lewy bodies brains. Issue 8 (9th July 2019) - Xu, Jinbin; Sun, Jianjun; Perrin, Richard J.; Mach, Robert H.; Bales, Kelly R.; Morris, John C.; Benzinger, Tammie L. S.; Holtzman, David M.
Abstract: Objective: Increased translocator protein (TSPO), previously known as the peripheral benzodiazepine receptor (PBR), in glial cells of the brain has been used as a neuroinflammation marker in the early and middle stages of neurodegenerative diseases, such as Alzheimer's disease (AD) and Dementia with Lewy Bodies (DLB). In this study, we investigated the changes in TSPO density with respect to late stage AD and DLB. Methods: TSPO density was measured in multiple regions of postmortem human brains in 20 different cases: seven late stage AD cases (Braak amyloid average: C; Braak tangle average: VI; Aged 74–88, mean: 83 ± 5 years), five DLB cases (Braak amyloid average: C; Braak tangle average: V; Aged 79–91, mean: 84 ± 4 years), and eight age‐matched normal control cases (3 males, 5 females: aged 77–92 years; mean: 87 ± 6 years). Measurements were taken by quantitative autoradiography using [ 3 H]PK11195 and [ 3 H]PBR28. Results: No significant changes were found in TSPO density of the frontal cortex, striatum, thalamus, or red nucleus of the AD and DLB brains. A significant reduction in TSPO density was found in the substantia nigra (SN) of the AD and DLB brains compared to that of age‐matched healthy controls. Interpretation: This distinct pattern of TSPO density change in late stage AD and DLB cases may imply the occurrence of microglia dystrophy in late stage neurodegeneration. Furthermore, TSPO may not only be a microglia activation marker in early stage AD and DLB, but TSPO may also be used to monitor microglia dysfunction in the late stage of these diseases.